Scholastic dictionary of idioms : more than 600 phrases, sayings & expressions - Terban, Marvin (New York : Scholastic, 1996)
An alphabetical listing of common figures of speech, along with their definitions and origins.
Includes index.
Wilson's Children.
Wilson's Junior High School.
Elem. School Library Collection.
5.5
3-6
Keywords: English language -- Terms and phrases -- Dictionaries, Juvenile; English language -- Idioms -- Dictionaries, Juvenile; Figures of speech -- Dictionaries, Juvenile; English language -- Idioms -- Dictionaries; Figures of speech -- Dictionaries; English language -- Dictionaries; English language -- Idioms; English language -- Terms and phrases -- Dictionaries; English language -- Idioms -- Dictionaries; Figures of speech -- Dictionaries